2019
DOI: 10.1111/bcp.14112
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated adverse reactions to vaccines

Abstract: Vaccination continues to be the single most important and successful public health intervention, due to its prevention of morbidity and mortality from prevalent infectious diseases. Severe immunologically mediated reactions are rare and less common with the vaccine than the true infection. However, these events can cause public fearfulness and loss of confidence in the safety of vaccination. In this paper, we perform a systematic literature search and narrative review of immune-mediated vaccine adverse events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
177
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(192 citation statements)
references
References 152 publications
5
177
2
8
Order By: Relevance
“…The active ingredient is rarely the cause and the focus should be directed at the many excipients usually present in vaccines 2 . A recent review of the literature showed that rare cases of immediate hypersensitivity reactions to excipients have been described for adjuvants/preservatives, antimicrobials and a single case of a reaction to polysorbate 80, a polymer with structural similarities to polyethylene glycol (PEG) 3,4 . Hypersensitivity reactions to vaccines containing gelatin and egg had only been described in patients with previous known hypersensitivity to gelatin and egg.…”
mentioning
confidence: 99%
“…The active ingredient is rarely the cause and the focus should be directed at the many excipients usually present in vaccines 2 . A recent review of the literature showed that rare cases of immediate hypersensitivity reactions to excipients have been described for adjuvants/preservatives, antimicrobials and a single case of a reaction to polysorbate 80, a polymer with structural similarities to polyethylene glycol (PEG) 3,4 . Hypersensitivity reactions to vaccines containing gelatin and egg had only been described in patients with previous known hypersensitivity to gelatin and egg.…”
mentioning
confidence: 99%
“…However, adverse reactions do occur and can include fever, febrile seizures, hypersensitivity reactions, and possibly a small increase in the risk of developing Guillain-Barre syndrome [217,218]. Several organizations, including the WHO, the European Union, the US government, and independent agencies have mechanisms in place for tracking vaccine safety [216,219,220]. In the United States, the Vaccine Adverse Event Reporting System passively documents post-licensure adverse events following vaccination administration [221].…”
Section: Increasing Vaccination Rates For Influenzamentioning
confidence: 99%
“…These cases of anaphylaxis raise more questions than they answer; however, such safety signals are almost inevitable as we embark on vaccination of millions of people, and they highlight the need for a robust and proactive “safety roadmap” to define causal mechanisms, identify populations at risk for such reactions, and implement strategies that will facilitate management and prevention ( Figure 1 ). 6 …”
mentioning
confidence: 99%
“…We can be reassured that vaccine-associated anaphylaxis has been a rare event, at one case per million injections, for most known vaccines. 6 Acute allergic reactions after vaccination might be caused by the vaccine antigen, residual nonhuman protein, or preservatives and stabilizers in the vaccine formulation, also known as excipients. 6 Although local reactions may be commonly associated with the active antigen in the vaccine, IgE-mediated reactions or anaphylaxis have historically been more typically associated with the inactive components or products of the vaccine manufacturing process, such as egg, gelatin, or latex.…”
mentioning
confidence: 99%
See 1 more Smart Citation